Pengembangan Peta Wisata Desa Olehsari melalui Program KKN Mahasiswa UINSA untuk Mendukung Kemajuan Desa Wisata - Melati, Seruni Kharisma; Junjunan, Mochammad Ilyas (Jurnal Pengabdian Masyarakat dan Lingkungan, 2026)
This community service aims to describe th contributon of the Student Community Service Program (KKN) of UIN Sunan Ampel (UINSA) in developing a tourism map to support the Olehsari Tourism Village. The method used is Participatory Action Research (PAR) with the stages of identifying potential, data collection and creating a digital map using Google My Maps. The result of this program is the creation of an interactive digital tourism map that makes it easier for visitors to explore various tourist attractions in Olehsari Village, such as natural tourism, culinary and home inustry. This map has successfully functioned as an effective promotional media and has contributed to increasing tourist visits. The conculision of this activity shows that the integration of the Tri Dharma of higher education through KKN with the real needs of the community can be effective catalyst for acceleration the development of tourism village. This digital tourism map is expected to be a sustainable tool for the community in managing and promoting the tourism potential of their village.